Comparison between results of optical and electrical measurements of free electron concentration in n-InAs specimens - Tatyana G. Yugova (Pensoft Publishers, 2021)
A theoretical model has been developed for determining the free electron concentration in n-InAs specimens from characteristic points in far IR reflection spectra. We show that this determination requires plasmon-phonon coupling be taken into account, otherwise the measured electron concentration proves to be overestimated. A correlation between the electron concentration Nopt and the characteristic wavenumber ν+ has been calculated and proves to be well fit by a third order polynomial. The test specimens have been obtained by tin or sulfur doping of indium arsenide. The electron concentration in the specimens has been measured at room temperature using two methods: the optical method developed by the Authors (Nopt) and the conventional four-probe Hall method (the Van der Pau method, NHall). The reflecting surfaces of the specimens have been chemically polished or fine abrasive ground. The condition Nopt > NHall has been shown to hold for all the test specimens. The difference between the optical and the Hall electron concentrations is greater for specimens having polished reflecting surfaces. The experimental data have been compared with earlier data for n-GaAs. A qualitative model explaining the experimental data has been suggested.